Volatility and diversification of exports: firm level theory and evidence - Vannoorenberghe, Gonzague; Zheng, Wang; Yu, Zhihong (Elsevier, 2016)
We show using detailed firm-level Chinese data that, among small exporters, firms selling to a more diversified set of countries have more volatile exports, while the opposite holds among large exporters. This apriori surprising result for small firms is robust to a wide array of specifications and controls. Our theoretical explanation for these observations rests on the presence of fixed costs of exports per destination and short run demand shocks. In this setup , the volatility of a firm's exports depends not only on the diversification of its destination portfolio but also on whether it exports permanently to all markets. Among all exporters, a more diversified pool of destinations makes the firm more likely to export occasionally to some markets, thereby raising export volatility.